Tibouchina sect. Diotanthera, Diplostegia, Pseudopterolepis, Purpurella e Simplicicaules, (Melastomataceae) no estado de São Paulo - Oliveira, Cristiane Melo Silva (2001)
Orientadores: Angela Borges Martins, Paulo Jose Fernandes Guimarães